Strategi Pembangunan e-Culture di Indonesia - Melkior N.N. Sitokdana; Andeka Rocky Tanaamah (Maranatha University Press, 2016)
Indonesia is famous for its rich culture; however the development process seems to be done partially and it causes serious globalization and modernization threats toward the existence of Indonesian cultural heritance. There is a solution that can be executed to protect our culture; by managing, documenting, spreading information and knowledge based on information and communication technology or it is usually called Electronic Culture (e-Culture). Therefore, a study that applies a qualitative and descriptive method was done by using SWOT analysis. The result of this study is a developing domain of e-culture in Indonesia. Besides that, there is a recommendation for Indonesian Government to establish a regulation and roadmap of e-culture development in order to protect Indonesian cultural heritance. As a result, it can be utilized for the sake of Indonesian people’s welfare. Keywords─ Culture, e-Culture, Strategy, SWOT Analysis.